Lean intervention improves patient discharge times, improves emergency department throughput and reduces congestion. Issue 5 (19th October 2016) - Beck, Michael J.; Okerblom, Davin; Kumar, Anika; Bandyopadhyay, Subhankar; Scalzi, Lisabeth V.
ABSTRACT: Objective : To determine if a lean intervention improved emergency department (ED) throughput and reduced ED boarding by improving patient discharge efficiency from a tertiary care children's hospital. Methods : The study was conducted at a tertiary care children's hospital to study the impact lean that changes made to an inpatient pediatric service line had on ED efficiency. Discharge times from the general pediatrics' service were compared to patients discharged from all other pediatric subspecialty services. The intervention was multifaceted. First, team staffing reconfiguration permitted all discharge work to be done at the patient's bedside using a new discharge checklist. The intervention also incorporated an afternoon interdisciplinary huddle to work on the following day's discharges. Retrospectively, we determined the impact this had on median times of discharge order entry, patient discharge, and percent of patients discharged before noon. As a marker of ED throughput, we determined median hour of day that admitted patients left the ED to move to their hospital bed. As marker of ED congestion we determined median boarding times. Results : For the general pediatrics service line, the median discharge order entry time decreased from 1:43pm to 11:28am (p < 0.0001) and the median time of discharge decreased from 3:25pm to 2:25pm (p < 0.0001). The percent of patients discharged before noon increased from 14.0% to 26.0% (p < 0.0001). The discharge metrics remained unchanged for the pediatric subspecialty services group. Median ED boarding time decreased by 49 minutes (p < 0.0001). As a result, the median time of day admitted patients were discharged from the ED was advanced from 5 PM to 4 PM. Conclusion : Lean principles implemented by one hospital service line improved patient discharge times enhanced patient ED throughput, and reduced ED boarding times.